MASLAHAH MURSALAH REVIEW OF ONLINE ZAKAT PRACTICES IN BAZNAS MALANG CITY - Anggit Wasesa Praja; Erfan Bahrudin; Ilham Harun (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThe practice of zakat online is the answer to technological developments. The benefit is that it can help the community be easier to pay zakat by being distributed indirectly, the practice of zakat online does not as smoothly as expected there are concerns in the community about pros and cons, especially in online zakat payment methods. The purpose of this study is to find out the practice of online zakat in the National Amil Zakat Agency (BAZNAS) of Malang City and find out how the practice of zakat online from the review of maá¹£laá¸¥ah mursalah. This research is a type of qualitative research using a normative approach. Data collection was used with literature studies and documentation. Based on the results of the study, it can be concluded that the practice of zakat online when viewed from the perspective of maá¹£laá¸¥ah mursalah then it is classified at the level of maá¹£laá¸¥ah hajjiyah (secondary needs) which is benefit as a refinement of primary needs that can facilitate can make it easier in muamalah relationships.Keywords: Online zakat; Akad; Maá¹£laá¸¥ah Mursalah.